Morpho-physiological seed diversity and viability of Indonesian cowpea (Vigna unguiculata) - ENY WIDAJATI; MUHAMAD SYUKUR; RIDWAN DIAGUNA; OKTI SYAH ISYANI PERMATASARI; ARYA WIDURA RITONGA; ZULFIKAR DAMARALAM SAHID; GAGAD RESTU PRATIWI; ANDI NADIA NURUL LATHIFA HATTA (Society for Indonesian Biodiversity, 2023)
Abstract. Widajati E, Syukur M, Diaguna R, Permatasari OSI, Ritonga AW, Sahid ZD, Pratiwi GR, Hatta ANNL. 2023. Morpho-physiological seed diversity and viability of Indonesian cowpea (Vigna unguiculata). Biodiversitas 24: 5319-5327. Cowpea is a legume with a potential nutritional content almost equivalent to soybeans; it can be developed as a substitute agent for raw materials for food processing. One of the factors in obtaining high cowpea production is to use of quality seeds. Our study aimed to evaluate the performance and morpho-physiological correlations and viability of cowpea seed collections from IPB University Bogor and the Indonesian Research Institute of Legume. We used ten genotypes of cowpea, which had superior seed information. The results showed that the ten cowpea genotypes had superior morpho-physiological and seed viability. The seed germination percentage was categorized as medium-high (>60%). Eight cowpea genotypes were grouped into one major group based on morpho-physiological characteristics and viability. Furthermore, positive correlations were found between the observed variables of seed viability (seed germination, seed growth speed, and seed vigor index). Our research results are useful as a source of genetic diversity for plant breeders in developing new superior varieties in the future. In addition, agronomists can use this information to plant cowpeas based on planting location.